Coumarin-surfactant modified polyoxometalate catalyzed cross dehydrogenative coupling of benzyl alcohol with the para-C–H of unprotected aniline. Issue 20 (24th September 2018) - Xu, Qian; Yu, Gang; Liu, Min; Peng, Chang; Banks, M. Katherine; Xu, Weijian; Wu, Ruoxi; Lu, Yanbing
Abstract : This paper presents a novel method for synthesizing para -aminobenzophenone and its derivatives ( p -ABPs) using a coumarin-surfactant modified polyoxometalate as the catalyst. Abstract : This paper presents a novel method for synthesizing para -aminobenzophenone and its derivatives ( p -ABPs) using a coumarin-surfactant modified polyoxometalate as the catalyst. Preliminary mechanistic studies indicate that the reaction has undergone an oxidative cross dehydrogenative coupling process. This method has the advantages of an easy process, a convenient raw material source, safe and green oxidants, and tolerances of several functional groups.